2020
DOI: 10.1101/2020.08.12.248468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Evidence for Biased Inhibition of G protein Signaling by YM-254890 in Human Coronary Artery Endothelial Cells

Abstract: Small molecular chemicals targeting individual subtype of G proteins including Gs, Gi/o and Gq has been lacking, except for pertussis toxin being an established selective peptide inhibitor of the Gi/o protein. Recently, a cyclic depsipeptide compound YM-254890 isolated from culture broth of Chromobacterium sp. was reported as a selective inhibitor for the Gq protein by blocking GDP exchange of GTP on the α subunit of Gq complex. However, functional selectivity of YM-254890 towards various G proteins was not fu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We found that T2R agonists denatonium benzoate and quinine, but not sodium benzoate, both increased apical DAF-2 fluorescence in a NOS-dependent manner, as responses were inhibited by L-NAME but not D-NAME (Figure 6B). These DAF-2 responses, likely reflecting NO diffusion into the ASL, were blocked by pretreatment (10 µM, 45 min) with GPCR G protein inhibitor YM-254890 (105)(106)(107) or HSP90 inhibitors geldanamycin, 17-AAG, or BIIB 021 (Figure 6C) but were not blocked by HSP70 inhibitor VER-15508. Like submerged H441s, we saw inhibition with eNOS siRNA but not with scramble, nNOS, or PAR-2 siRNA (Figure 6D).…”
Section: Hsp90 Inhibition Reduces Endogenous Enos Function In H441 Cellsmentioning
confidence: 98%
“…We found that T2R agonists denatonium benzoate and quinine, but not sodium benzoate, both increased apical DAF-2 fluorescence in a NOS-dependent manner, as responses were inhibited by L-NAME but not D-NAME (Figure 6B). These DAF-2 responses, likely reflecting NO diffusion into the ASL, were blocked by pretreatment (10 µM, 45 min) with GPCR G protein inhibitor YM-254890 (105)(106)(107) or HSP90 inhibitors geldanamycin, 17-AAG, or BIIB 021 (Figure 6C) but were not blocked by HSP70 inhibitor VER-15508. Like submerged H441s, we saw inhibition with eNOS siRNA but not with scramble, nNOS, or PAR-2 siRNA (Figure 6D).…”
Section: Hsp90 Inhibition Reduces Endogenous Enos Function In H441 Cellsmentioning
confidence: 98%
“…YM-254890, the small molecule Gq/11 inhibitor (500 nM, (Uemura et al, 2006)) reduced maximum AEA-mediated block of VGSC currents from 86% (n = 8) to 41% (Figure 3G,H; n = 5; P = 0.049). This substantial attenuation of the action of AEA suggests a role for Gq/11, however YM-254890 may also inhibit other Gproteins (Peng et al, 2021). Taken together, our experiments using Cnr1 -/neurons, CB1 antagonists, and inhibitors of G-proteins indicate that CB1 is responsible for the majority of inhibition of VGSC currents by AEA and that this is mediated via a GTP-dependent mechanism.…”
mentioning
confidence: 57%
“…The effectiveness of GDPβS and G-alpha inhibitor, YM-254890, at inhibiting the action of AEA on VGSC currents, also support an indirect GPCR mediated action (Figures 2,3). YM-254890 inhibits Gq/11 and Gs by preventing GDP exchange for GTP on these alpha subunits, and potentially also exhibits biased inhibition of Gi/o (Peng et al, 2021;Taniguchi et al, 2003). That YM-254890 attenuated but did not ablate AEA block, implies additional involvement of alpha subunits other than those sensitive to YM-254890.…”
Section: Cb1 Is a Key Player In Aea Inhibition Of Vgsc Currentsmentioning
confidence: 98%
“…A recent study used the Gα q ‐selective inhibitor YM‐254890 and the adenylate cyclase inhibitor MDL‐12330A to demonstrate that, under normal circumstances, GLP‐1‐induced insulin secretion is primarily Gα s ‐mediated, but Gα q plays a more important role when beta cells are chronically depolarised, for example, with sulphonylurea treatment or sustained hyperglycaemia (Oduori et al, 2020). Nevertheless, in the context of the prevailing view that GLP‐1 receptor acts predominantly via Gα s , concerns about the specificity of YM‐254890 (Peng et al, 2020) mean that additional independent lines of evidence are needed to verify the importance of Gα q in GLP‐1 receptor signal transduction.…”
Section: Measuring Glp‐1 Receptor Biased Agonism In Vitromentioning
confidence: 99%